Geostatistical Borehole Image‐Based Mapping of Karst‐Carbonate Aquifer Pores. Issue 2 (14th July 2015) - Sukop, Michael C.; Cunningham, Kevin J.
Abstract: Quantification of the character and spatial distribution of porosity in carbonate aquifers is important as input into computer models used in the calculation of intrinsic permeability and for next‐generation, high‐resolution groundwater flow simulations. Digital, optical, borehole‐wall image data from three closely spaced boreholes in the karst‐carbonate Biscayne aquifer in southeastern Florida are used in geostatistical experiments to assess the capabilities of various methods to create realistic two‐dimensional models of vuggy megaporosity and matrix‐porosity distribution in the limestone that composes the aquifer. When the borehole image data alone were used as the model training image, multiple‐point geostatistics failed to detect the known spatial autocorrelation of vuggy megaporosity and matrix porosity among the three boreholes, which were only 10 m apart. Variogram analysis and subsequent Gaussian simulation produced results that showed a realistic conceptualization of horizontal continuity of strata dominated by vuggy megaporosity and matrix porosity among the three boreholes.